1993
DOI: 10.1007/bf00217346
|View full text |Cite
|
Sign up to set email alerts
|

Molecular defect in human erythropoietic protoporphyria with fatal liver failure

Abstract: We investigated the molecular basis of ferrochelatase in a Japanese patient with erythropoietic protoporphyria (EPP), complicated by fatal liver failure, and defined a novel point mutation in the ferrochelatase gene. cDNAs were synthesized using Epstein-Barr-virus-transformed lymphoblastoid cells from the proband. cDNA clones encoding ferrochelatase in the proband were isolated by amplification using the polymerase chain reaction. There were two sizes of ferrochelatase cDNAs; one was normal in size, the other … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

1994
1994
2006
2006

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(13 citation statements)
references
References 13 publications
1
12
0
Order By: Relevance
“…The first case, reported by Nakahashi and co-workers (25), had a mutation at the donor site of intron 9 which resulted in the deletion of exon 9. Schneider-Yin et al reported a patient with a point mutation (175C→T) that caused a stop codon that produced a truncated protein (43).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The first case, reported by Nakahashi and co-workers (25), had a mutation at the donor site of intron 9 which resulted in the deletion of exon 9. Schneider-Yin et al reported a patient with a point mutation (175C→T) that caused a stop codon that produced a truncated protein (43).…”
Section: Discussionmentioning
confidence: 99%
“…Sarkany et al described two siblings that were compound heterozygotes for an exon 10 deletion and developed liver failure in adolescence (30); and proposed that recessive inheritance may be an important factor that predisposes patients with protoporphyria to develop liver disease. However, the patients reported by Nakahashi et al (25) and Schneider-Yin et al (43) both had autosomal dominant inheritance (44). Moreover, no patient in the present study had evidence for recessive inheritance.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A genetic defect in human ferrochelatase causes the disease erythropoietic protoporhyria. Exon deletions are common causes of this disease (32)(33)(34)(35)(36). A set of mutants containing individual deletions of exons 3 through 11 was previously constructed to study the underlying biochemical nature of erythropoietic protoporhyria (37).…”
Section: Characterization Of the C196s Mutant Of Humanmentioning
confidence: 99%
“…[7][8][9] Chronic liver disease is associated with marked PPIX accumulation in liver, which can begin insidiously. 10 The source of the excessive amounts of PPIX in patients with EPP is, according to most authors, the bone marrow, and mild anemia is observed in 20% to 50% of EPP patients. 11,12 Pathogenesis of the hematologic symptoms is not yet fully understood, and controversial hypotheses have been reported about its origin.…”
Section: Introductionmentioning
confidence: 99%